Sentir, Significar e Construir Conhecimento com Base nos Erros - Bianchini, Luciane Guimarães Batistella; Vasconcelos, Mario Sergio (Universidade Federal do Rio Grande do Sul - Faculdade de Educação, 2017)
Abstract: By means of Piaget's critical clinical method, the study investigated the meanings assigned to mistakes by four students in different activities and interactive situations. The research also analyzed the results of using self-regulatory situations in understanding mistakes initially committed by the students. Data collection instruments consisted of games, video recordings, diaries and interviews. Following intervention, the students were able to recognize their competence, establish positive interactions within the group, and avoid viewing mistakes as obstacles to learning. We concluded that the meanings assigned to mistakes depend on certain variables, among them feelings nurtured by the individuals about themselves, the other, and the object of knowledge.

Resumo: Por intermédio do método clínico crítico piagetiano, investigou-se as significações, atribuídas ao erro por quatro estudantes em diferentes atividades e situações interativas. Também foram verificados os resultados do emprego de situações autorreguladoras na compreensão do erro inicialmente apresentado por eles. Os instrumentos para a coleta de dados consistiram em jogos, videogravações, diários e entrevistas. Após intervenção, os alunos passaram a se perceber competentes, estabelecer interações positivas no grupo e deixar de conceber o erro como uma ação impeditiva do aprender. Concluiu-se que as significações de erro são dependentes de algumas variáveis; entre elas, os sentimentos nutridos pelos sujeitos sobre si, o outro e o objeto de conhecimento.
Evoked Feelings, Assigned Meanings and Constructed Knowledge Based on Mistakes
Keywords: Jean Piaget; Mistakes; Meanings; Learning; Jean Piaget; Erro; Significações; Aprendizagem